2019
DOI: 10.1029/2019gl082172
|View full text |Cite
|
Sign up to set email alerts
|

The 2005–2016 Trends of Formaldehyde Columns Over China Observed by Satellites: Increasing Anthropogenic Emissions of Volatile Organic Compounds and Decreasing Agricultural Fire Emissions

Abstract: We use 2005–2016 observations of formaldehyde (HCHO) columns over China from the OMI, GOME‐2, and SCIAMACHY satellite instruments to evaluate long‐term trends in emission inventories of volatile organic compounds (VOCs) that affect air quality. The observations show large increases over 2005–2016 in the North China Plain (+1.1 ± 0.5% a−1 relative to 2005) and the Yangtze River Delta region (+1.5 ± 0.4% a−1 relative to 2005), consistent with the trend of anthropogenic VOC emissions in the Multi‐resolution Emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 74 publications
(107 reference statements)
5
74
0
2
Order By: Relevance
“…We do not see a significant deviation in the model from the observations over this region indicating that no noticeable efforts on controlling VOC emissions in NCP and YRD have been made which is very likely due to the fact that the recent regulations over China have overlooked cutting emissions from several industrial sectors 310 prior to 2016 ]. This finding lines up with results reported by Souri et al [2017] and Shen et al [2019]. We observe both underestimated and overestimated values in the simulated HCHO columns over areas in South Korea and Japan.…”
Section: Hcho 290supporting
confidence: 93%
See 2 more Smart Citations
“…We do not see a significant deviation in the model from the observations over this region indicating that no noticeable efforts on controlling VOC emissions in NCP and YRD have been made which is very likely due to the fact that the recent regulations over China have overlooked cutting emissions from several industrial sectors 310 prior to 2016 ]. This finding lines up with results reported by Souri et al [2017] and Shen et al [2019]. We observe both underestimated and overestimated values in the simulated HCHO columns over areas in South Korea and Japan.…”
Section: Hcho 290supporting
confidence: 93%
“…In contrast, enhancements of the emissions are evident at higher latitudes. We observe that the dominantly anthropogenic VOC emissions over NCP increase (~25%) after the adjustment highlighting the minimal efforts made 390 to reduce this particular source of emissions [Souri et al, 2017;Shen et al, 2019]. For instance, Stavrakou et al [2017] reported ~6% increases in anthropogenic VOC emissions over China from 2010 to 2014.…”
Section: Nox 325mentioning
confidence: 86%
See 1 more Smart Citation
“…S7, S8, and S9. The TCCON stations include Indianapolis (Iraci et al, 2017a), Manaus (Dubey et al, 2017a), Sodankylä (Kivi et al, 2017), Lauder (Sherlock et al, 2017a, b), Burgos (Morino et al, 2018), Ascension Island (Feist et al, 2017) Author contributions. BZ, FC, and PC designed the study.…”
Section: Appendix A: Region Splitting In This Studymentioning
confidence: 99%
“…Here, the OMI and GOME-2A observational operators (a priori profiles and averaging kernels) are applied to the model, so that the HCHO profile assumptions are indeed consistent in both cases. Recent work by Shen et al (2019) concluded that the Zhu et al (2016) correction was also valid over China, suggesting that it may be uniform and thus likewise apply over India. A comparison of the updated QA4ECV HCHO products (used here) versus the v14 products (evaluated previously) over our Indian domain yields a slope of 1.31 (d[QA4ECV]/d[v14]) and correlation of 0.92 for OMI and a slope of 1.13 and correlation of 0.84 for GOME-2A.…”
Section: Hcho Column Observations Over the Indian Subcontinentmentioning
confidence: 99%